Immunoproteomics enable broad identification of new Aspergillus fumigatus antigens in severe equine asthma - Jentsch, Maria-Christin; Lübke, Sabrina; Schrödl, Wieland; Volke, Daniela; Krizsan, Andor; Hoffmann, Ralf; Kaiser-Thom, Sarah; Gerber, Vinzenz; Marti, Eliane; Wagner, Bettina; Schnabel, Christiane L. (Frontiers in Immunology, 2024)
Severe equine asthma (SEA) is a common chronic disease of adult horses with characteristic recurrent airway obstruction and similarities to neutrophilic asthma in humans. As an extrinsic stimulus, hay dust exposure is a major risk factor and induces acute exacerbation in susceptible horses. However, single inducing agents of SEA have hardly been identified on a molecular basis. Aspergillus fumigatus (A. fumigatus) is a common mold species in hay and has been described as a major provoking agent of SEA. Aiming to identify disease-relevant antigens, we analyzed A. fumigatus in an immunoproteomics approach on two-dimensional immunoblots of A. fumigatus protein probed with serum from environmentally matched asthmatic and healthy horses (n=5 pairs). A. fumigatus binding serum immunoglobulins (Pan-Ig), and the isotypes IgG4/7 and IgG3/5 were quantified for each protein spot and then compared between asthmatic and healthy horses. For 21 out of 289 spots serum immunoglobulins (Ig) binding was different between the two groups for Pan-Ig or the isotypes. If differences were detected, Pan-Ig and IgG4/7 binding to the proteins were lower, while IgG3/5 binding was higher with asthmatic - than healthy horse sera. Proteins were extracted from the 21 spots of interest and analyzed by liquid chromatography mass spectrometry. Eight prioritized proteins (candidate antigens) were expressed as recombinant proteins. Some of these have been previously described as major or minor A. fumigatus allergens, alongside other proteins, most with hydrolase activity. Recombinant candidate antigens were tested on 1D immunoblots to confirm their relevance as antigens by serum antibody binding. Four proteins (beta-hexosaminidase, class II aldolase/adducin domain protein, glucoamylase, peptide hydrolase B0XX53) showed different antibody binding characteristics between asthmatic and healthy horses and are likely relevant antigens in SEA. Their identification can provide the basis for innovative diagnostics, prevention or therapeutic approaches. Additionally, a more profound understanding of SEA and its potential underlying mechanisms can be established. Elevated serum IgG3/5 antibodies correlate with T helper cell 2 responses in other equine pathologies, and the recombinant SEA antigens developed here can become instrumental to analyze the involvement of SEA-specific T cell responses and Ig responses in future studies.